COMMUNICATION TECHNOLOGIES IN TEACHING ENGLISH - Nazarov, Rustam (Журнал иностранных языков и лингвистики, 2023)
The present article casts the light on the ICT tools that can help in the development of English language learning and teaching processes to show how technology affects second/foreign language education and how it can be used effectively in the secondary EFL (English as a Foreign Language) classroom.